EFEKTIVITAS PENYULUHAN PEER GROUP DENGAN PENYULUHAN OLEH PETUGAS KESEHATAN TERHADAP TINGKAT PENGETAHUAN TENTANG MENARCHE - ririn tri rahayu; cokro aminoto; M. madkhan Anis (Jurnal Ilmiah Kesehatan Keperawatan, 2011)
One effort to change behavior in health is by increasing knowledge. Increased knowledge of first menstruation is through counseling.This research is aimed to examine issues concerning the effectiveness of peer group counseling and counseling by health workers to knowledge level about the first menarche on female students of MTS KHR ILYAS Tambakrejo Village Buluspesantren Kebumen 2010. This is a quasi experimental research that used in Separate sample pretest-postest. The populations in this study were the seventh and eighth grade female students MTS KHR Ilyas Tambakrejo Village (48 female students). The samples were taken by Non-Probability Sampling (total sampling) technique. To examine the effectiveness of counseling the researcher conducted paired t-test test Statistical analysis with paired t-test test test statistics obtained by the peer group with a t value <t table (-7.597 <2.069) and p value 0.000 <0.05 means that there was no difference between the level of knowledge before and after obtaining counseling about the health of first menarche by age peer group in MTs KHR Ilyas Tambakrejo Village. And from the results of statistical tests by health officials found that the value of the t <t table (-4.928 <2.069) and 0.000 p value <0.05 means that there was no difference between the level of knowledge before and after obtaining counseling about the health of first menstruation by health workers in the MTs KHR Ilyas Tambakrejo Village. There was no difference between peer group counseling and counseling by health workers. Both were equally effective for increasing knowledge about the first menarche on female students of MTS KHR ILYAS Tambakrejo Village Buluspesantren Kebumen.   Keywords: Counseling, peer group, health provider, the level of knowledge.